Progressive resistance training in patients with hip dysplasia: A feasibility study - Louise Mortensen; Jeppe Schultz; Anton Elsner; Stig S. Jakobsen; Kjeld Søballe; Julie S. Jacobsen; Signe Kierkegaard; Ulrik Dalgas; Inger Mechlenburg (Medical Journals Sweden, 2018)
Objectives: To examine whether progressive resistance training is feasible in patients with symptomatic hip dysplasia scheduled for periacetabular osteotomy. A secondary objective was to investigate patient-reported outcomes, functional performance and hip muscle strength. Design: Feasibility study. Patients and methods: Seventeen patients (median age 28 years, range 22-40 years) performed 8 weeks (20 sessions) of supervised sessions of progressive resistance training. Training-adherence, number of dropouts and adverse events, and visual analogue scale scores on pain were registered. Patients completed the Hip and Groin Outcome Score, performed 2 hop-tests, and hip peak torque was assessed by isokinetic dynamometry. Results: Training-adherence was 90.3±9%. Few and minor adverse events were observed, one patient dropped out and acceptable pain levels were reported during the intervention. Scores on 4 out of 6 subscales on patient-reported outcome improved (p < 0.05), as did standing distance jump (12.2%, 95% confidence interval (CI) [1.3, 23.0]), countermovement jump (25.1%, 95% CI [1.3, 48.8]). Isokinetic concentric hip flexion peak torque showed significant improvements (16.6%, 95% CI [4.6, 28.6]) on the affected side while isometric hip flexion (10.9%, 95% CI [0.3, 21.6]) improved on the non-affected side. Conclusion: Supervised progressive resistance training is feasible in patients with hip dysplasia. The intervention may improve pain levels, patient-reported outcomes, functional performance and hip flexion muscle strength.